Strategies of Indian IT Industry in Hypercompetitive Global Economy : Case Study of TCS, Infosys and Wipro - Kirubakaran, Vasantha Malar (2011)
The business ecosystem worldwide has been completely transformed by the revolution of economies and the emergence of digital firms, which was triggered by the wave of globalisation and the emergence of information technology which has turned our world truly into a global village. Realising the potential of its human resource, India emerging from its colonial past, relying on an agrarian based economy now seeks dominance in the information age through the liberalization of the markets by globalisation. With the evolution of the Information Technology Industry, India’s economy caught a rapid pace. Indian IT Industry leaders like Wipro Technologies, Tata Consultancy Services and Infosys Technologies not only seized opportunities but also have made an outstanding performance since their inception cruising at high speed on the information superhighway. Currently India is looked upon not only as a driver of corporate growth agendas and but also as an excellent hub for business ownership, research and development and innovation. Contribution of the above mentioned three Indian IT firms towards all this has been splendid and significant.A tale as old as time, the global markets have induced uncertainty into the business of even the most successful companies around the world. Globalization and internationalisation of well established companies have led to high level of competition worldwide. In such scenario, all the firms worldwide had to rethink their business strategies to fit the highly volatile and competitive global market space. It is a well known fact that any wave in global economy hits the globally established companies from developing economies the worst. Inspite of the turbulence and instability that the global economy has faced in past decades, it seems that Indian IT industry has been consistently performing well. In this project, we have attempted to study the successful strategies that the top three Indian IT firms – TCS,Infosys and Wipro, have taken to overcome this increasing pressure of globalization and rising global competition to perform remarkably well.